Sistem Informasi Pariwisata Bangka Belitung Berbasis Website - Bayu Pratama; Ahmat Josi; Yang Anggita Rindri (JSK ( Jurnal Sistem Informasi dan Komputerisasi Akuntansi ), 2022)
The Bangka Belitung Islands is one of the provinces in Indonesia that is in the form of islands. The province, which consists of 2 main islands and hundreds of small islands, has a lot of potential especially in the tourism sector. Land surrounded by vast oceans has led the Province of the Bangka Belitung Islands to be awarded the potential of tourist attractions especially beaches and resorts that are very diverse and can be enjoyed by the community. However, tourist information obtained from official local government websites is still incomplete and not specific. For this reason, through this research a website-based Bangka Belitung Tourism Information System will be built with a simple display, this aims to make it easier for people to find information with a design that is not confusing. The creation of a website-based barrage tourism information system was built using the PHP programming language and framework codeigniter 4 and mysql. This website-based barrage tourism information system was built so that it can convey information about tourism in Bangka Belitung in the form of a place name, location based on village or outpouring along with sub-district and district, supplemented by tourist site recommendations and also comments and suggestions from other communities who have visited the tourist site. In addition, there is news about tourism in Bangka Belitung that can be read by the public, information about tour guides that have been verified by the admin as well as information about events in the form of tradition, custom and others.